Music and Text in Elisabeth Lutyens's Wittgenstein Motet - Parsons, Laurel (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
Although Elisabeth Lutyens (1906-83) was a pioneer of British twentieth-century music, her work is relatively unknown in North America. This article begins with an introduction to her life and compositions, before going on to a detailed analysis of text-music relations in selected passages of her Motet, op. 27 (1953). The analysis forms the basis for a discussion of the concept of text as representation of music: Lutyens began to compose the music of the Motet first, and chose its text—excerpts from the Tractatus logico-philosophicus (1921) by the Austrian-born English philosopher Ludwig Wittgenstein (1889-1951)—because it seemed a fitting expression of the musical ideas that had already begun to develop.